Radial basis functions for color conversion - Qiao, Yue, author; Kirby, Michael, advisor (Colorado State University. Libraries, 2008)
The most difficult and challenging task in color printing is to reduce costs while maintaining superior quality. This dissertation proposes significant enhancements to printer color conversion techniques including accurate nonlinear models that incorporate perceptual color difference metrics, lossless gray component replacement (GCR) transformations, optimized toner saving algorithms and numerical/perceptual based gamut mapping methods. Radial Basis Functions (RBFs) combined with the Lp norm approximation with emphasis on L1, L2, and L∞ were developed for color conversion. The exchange algorithm was employed in the L∞ and L1 approximations with RBFs that satisfy the Haar condition. Both the Barrodale and Phillips (BP) algorithm for solving the dual problem and the Bartels and Conn's (BC) algorithm for solving the primal were extended to multidimensional color conversion. A new approach for lossless GCR was achieved by finding one dimensional color manifolds in the CMIYK color space using multidimensional optimization techniques. We proposed objective functions for toner savings, cost savings, etc., with no quality degradation. The color conversion with the toner/ink limitation problem was solved via both L1 and L∞ approximation algorithms in the neutral and saturated color regions respectively. The L1 algorithm was a modified Barrodale and Roberts (BR) primal algorithm with an added constraint, while the L∞ algorithm was developed based on the BP dual algorithm which extended the three-stage algorithm to a four-stage algorithm. A novel gamut mapping algorithm was developed based on the numerical model guided by a perceptual color difference model. The direction of the gamut mapping is not fixed as in other methods. The algorithm transformed a connected out-of-gamut colors to connected colors around the boundary of the device gamut. The out-of-gamut colors in a small neighborhood vary continuously and smoothly. Our results indicated that the color conversion quality was significantly improved. The lossless GCR algorithm is accurate and efficient. Both the BP and BC algorithms for solving the toner/ink limitation are able to convert colors from CIELab to CMY with any given toner/ink limitation. We foresee this research will have significant impact on the color reproduction industry.
Keywords: color conversion; gray component replacement; radial basis functions; applied mathematics